Pengaruh Stadium HIV terhadap Infeksi Oportunistik, Penggunaan Antiretroviral dan Antibiotik pada Pasien HIV di Rumah Sakit X Kota Malang - Nurma Puspita Asis; Andri Tilaqza; Hardadi Airlangga (Jurnal Kedokteran Komunitas, 2020)
Introduction: Human Immunodeficiency Virus (HIV) is a retrovirus group in the family Retroviridae, a genus of lentiviruses that attack white blood cells that cause a decrease in immunity in humans.The immunity of HIV patients can be assessed based on CD4 levels and clinical symptoms which are divided into four clinical stages of HIV. Each level of HIV stage can affect the use patterns of antiretrovirals and antibiotics used by HIV patients during treatment. This study aims to determine the relationship between the effect of HIV staging on antiretroviral profiles, types of opportinistic infections that accompany, antibiotics used for opportunistic infections and the duration of antibiotic administration used by HIV patients in one hospital in Malang.Method: Non-experimental research was carried out in a Analytic Observational Cross Sectional Retrospective study using a Descriptive Analytic design, using a total sampling method by taking secondary data or medical records on HIV patients at Hospital X Malang in 2015-2018.Results: The total population are 112 medical records and data that inclusion criteria are 73 medical records obtained by the HIV stadium did not affect the use of ARVs  HIV stage did not affect the use of antiretroviral drugs (p = 0.473) (p> 0.05), opportunistic infections (p = 0.135) (p> 0.05), antibiotic use (p = 0.175) (p> 0.05) and duration of antibiotic administration (p = 0.864) (p> 0.05).Conclusion: HIV stage does not affect the pattern of ARV use, opportunistic infections that accompany patients, patterns of antibiotic use and duration of antibiotic administration of HIV patients at VCT Hospital X Malang in 2015-2018.Keywords: HIV stage, ARVs, opportunistic infections, antibiotics